PENGARUH KEPERILAKUAN ORGANISASI TERHADAP KEGUNAAN SISTEM AKUNTANSI KEUANGAN RUMAH SAKIT DENGAN KONFLIK KOGNITIF DAN AFEKTIF SEBAGAI VARIABEL INTERVENING (STUDI PADA RUMAH SAKIT PEMERINTAH DI KOTA PEKANBARU) - Rheny Afriana Hanif; R. Adri Satriawan '; Triyanto Hadi Saputra (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This research aims to test the influence of organizational behavior factors including support, utilization of technology, clarity of purpose and usefulness of training system of financial accounting of hospital, as well as the indirect effects of cognitive and affective conflict conflict in system implementation with regard to the individual issues that did not happen the rejection system developed.. This research was conducted in the city of Pekanbaru with the respondent Employees the financial section of the hospital. The sample in this study is taken by the method of Random sampling a number of 160 respondents of the Finance Manager population numbers. Research methods used in this study using quantitative research methods and analysis of the path (path analysis) to test the hypothesis that applied. The results showed that the clarity of the objective effect on cognitive conflict with sig. 0.000. Clarity of purpose to affective conflict with sig. 0.000. Support supervisor, clarity of purpose and training as well as affective conflict affect the usefulness of the financial accounting of hospital system with sig. each 0,049; 0.31; 0,19; 0.000. Both cognitive and affective conflict can be penyela between the relationship of organizational behavior and usability of financial accounting system in hospitals.Kata Kunci : organizational behavior Factors, cognitive, affective conflict conflict, financial accounting of hospital system.